Organ chip research in Europe: players, initiatives, and policies - da Silva, Renan Gonçalves Leonel; Blasimme, Alessandro (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Organ chips are microfabricated devices containing living engineered organ substructures in a controlled microenvironment. Research on organ chips has increased considerably over the past two decades. Aim: This paper offers an overview of the emerging knowledge ecosystem of organ chip research in Europe. Method: This study is based on queries and analyses undertaken through the bibliometric software Dimensions.ai. Results: Organ chip research has been rapidly growing in Europe in recent years, supported by robust academic science consortia, public-private initiatives, dedicated funding, and science policy instruments. Our data shows that previous investment in basic and fundamental research in centers of excellence in bioengineering science and technology are relevant to future investment in organ chips. Moreover, organ chip research in Europe is characterized by collaborative infrastructures to promote convergence of scientific, technical, and clinical capabilities. Conclusions: According to our study, the knowledge ecosystem of organ chip research in Europe has been growing sustainably. This growth is due to relevant institutional diversity, public-private initiatives, and ongoing research collaborations supported by robust funding schemes.